2008
DOI: 10.1186/1746-1340-16-1
|View full text |Cite
|
Sign up to set email alerts
|

Breast size, bra fit and thoracic pain in young women: a correlational study

Abstract: IntroductionA single sample study was undertaken to determine the strength and direction of correlations between: a) breast size and thoracic spine or posterior chest wall pain; b) bra fit and thoracic spine or posterior chest wall pain and; c) breast size and bra fit, in thirty nulliparous women (18–26 years), with thoracic spine or posterior chest wall pain, who wore bras during daytime.MeasuresPain (Short Form McGill Pain Questionnaire), bra size (Triumph International), bra fit (Triumph International).Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 20 publications
0
72
2
2
Order By: Relevance
“…It is particularly important for larger-breasted women (D cup and above) to wear a well-fitted and supportive bra, yet they are more likely to have an incorrect fit due to their breasts being ptotic and bulbous (Pechter 1998, Greenbaum et al 2003, McGhee et al 2006, Wood et al 2008. It is not clear whether there is a relationship between a woman's age and the effectiveness of the traditional bra fitting method.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is particularly important for larger-breasted women (D cup and above) to wear a well-fitted and supportive bra, yet they are more likely to have an incorrect fit due to their breasts being ptotic and bulbous (Pechter 1998, Greenbaum et al 2003, McGhee et al 2006, Wood et al 2008. It is not clear whether there is a relationship between a woman's age and the effectiveness of the traditional bra fitting method.…”
Section: Introductionmentioning
confidence: 95%
“…Regardless of how good the design of the bra, if the size is wrong, then it will not provide effective support (Page and Steele 1999). Despite this, it has been suggested that 70 to 100% of women are wearing the wrong-sized bra (Pechter 1998, Greenbaum et al 2003, Wood et al 2008. A correctly fitting and supporting bra is essential to good health; it can alleviate breast pain (Wilson and Sellwood 1976, BeLieu 1994, Hadi 2000, Smith et al 2004, allow women to exercise in greater comfort (Mason et al 1999, White et al 2009) and reduce the need for breast reduction surgery (Greenbaum et al 2003).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Poorly fitting bras lead to physical discomfort and can cause serious health problems such as muscle fatigue or pain. Producing well-fitting bras has been a challenge to manufacturers and retailers (Wood et al, 2008). Public service agencies and bra companies recommend various methods or formulas to help women select the correct bra size (Chen et al, 2011).…”
Section: Bra Cup Size and Fitmentioning
confidence: 99%
“…As a result of this, incorrect bra size may cause muscular and nerve problems [25]. Problematic bra fitting substantially increases in larger breasted women [11].…”
Section: Introductionmentioning
confidence: 99%